Energy Efficiency and Pollution Control Through ICTs for Sustainable Development - Popkova, Elena G.; Inshakova, Agnessa O.; Bogoviz, Aleksei V.; Lobova, Svetlana V. (Frontiers in Energy Research, 2021)
The goal of this paper is to prove the necessity for a more thorough consideration and more active use of the modern ICTs for the technological support for the practical implementation of the SDGs’ ecological block in the aspect of the increase of energy efficiency and environmental pollution control. The originality of this paper is as follows: it develops a proprietary methodology of evaluating the technical readiness (level of the development of ICTs) for implementing the ecological block of the SDGs, which envisage the increase of energy efficiency and the growth of environmental pollution control. The highest (but moderate) technological readiness to implement the ecological block of the SDGs among developed countries has been shown by Canada (14.42 points) and Denmark (11.03 points), among developing countries – China (7.72 points). As a result, it has been proved that UCTs are a perspective tool of the practical implementation of the ecological block of the SDGs, stimulating the increase of energy efficiency and improving the environment pollution control. For developed countries, it is recommended to increase the use of Big data and AI analytics by 90.36% and increase the use of ICTs in E-government by 89.74%. This paper’s contribution to literature consists in filling the gap of the uncertainty (underdevelopment) of the tools for practical implementation of the SDGs ecological block. This paper has demonstrated the substantial potential of ICTs in the stimulation of the growth of energy efficiency and reduction of environmental pollution in developed and developing countries.